Конкурентна культура в системі заходів конкурентної політики - Филюк, Г.М. (Економічна теорія, 2011)
Зроблено спробу комплексного аналізу концептуальних засад конкурентної культури. Визначено основні причини формування конкурентної культури на сучасному етапі. Розглянуто проблеми формування конкурентної культури в Україні та окреслено шляхи їх подолання. A contribution is made into a complex analysis of conceptual foundations of the culture of competition. The main causes of the formation of the culture of competition in modern conditions are defined. The problems of formation of competition culture in Ukraine are reviewed and the ways of resolving them are outlined.